Lattice constellations matched to GF(p) - Favareto, Osvaldo Milaré [UNESP]; Da Nóbrega Neto, Trajano Pires [UNESP]; Interlando, J. Carmelo [UNESP]; Palazzo Jr., Reginaldo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1997)
Signal sets matched to the additive group of GF(p) under the Mannheim distance are constructed. Such constellations are obtained via the ring of algebraic integers of an extension K=Q(√d) of Q, Where d=-1 or d=-3. The associated lattice constellations are suitable for Rayleigh fading channels because of their high spectral efficiency. © 1997 IEEE.